2010
DOI: 10.5751/es-03715-150433
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Barriers to Climate Change Adaptation in U.S. National Parks and Forests

Abstract: ABSTRACT. Climate change will increasingly challenge ecosystem managers' ability to protect species diversity and maintain ecosystem function. In response, the National Park Service and the United States Forest Service have promoted climate change adaptation as a management strategy to increase ecosystem resilience to changing climatic conditions. However, very few examples of completed adaptation plans or projects exist. Here, we examine managers' perceptions of internal and external institutional barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 11 publications
4
85
0
Order By: Relevance
“…These findings are concerning because it has been suggested that perceptions of barriers can limit action just as strongly as actual barriers, even in cases in which both sufficient capacity and resources to adapt exist (Adger et al 2007). Similar findings have also been reported in the United States, where it was found that internal barriers, such as unclear mandates from senior staff, combined with bureaucratic rules and procedures, were perceived by government officials to be a significant barrier (Jantarasami et al 2010). Accordingly, to overcome such barriers, government agencies should establish a clear agency mandate in relation to climate adaptation and give adequate resources to the implementation of the mandate, so that staff feel empowered to implement climate adaptation initiatives.…”
Section: The Risks Of Climate Changesupporting
confidence: 50%
“…These findings are concerning because it has been suggested that perceptions of barriers can limit action just as strongly as actual barriers, even in cases in which both sufficient capacity and resources to adapt exist (Adger et al 2007). Similar findings have also been reported in the United States, where it was found that internal barriers, such as unclear mandates from senior staff, combined with bureaucratic rules and procedures, were perceived by government officials to be a significant barrier (Jantarasami et al 2010). Accordingly, to overcome such barriers, government agencies should establish a clear agency mandate in relation to climate adaptation and give adequate resources to the implementation of the mandate, so that staff feel empowered to implement climate adaptation initiatives.…”
Section: The Risks Of Climate Changesupporting
confidence: 50%
“…Internal promotion procedures that reward loyalty or focus on achieving administratively defined targets, rather than creating successful natural resource outcomes, may also incentivize individuals not to recognize or question PEK (Weiss 1988, Teodoro 2011. Barriers to knowledge exchange, similar to those that may have contributed to development of PEK, may be partially responsible for the difficulty that government agencies are currently encountering with the development and implementation of climate change planning (Jantarasami et al 2010, Archie et al 2012). The major barriers identified for the development of climate change programs include unclear mandates and implementation procedures from upper administration, insufficient delegation of authority, and inadequate knowledge.…”
Section: Opportunities and Barriers For Knowledge Exchangementioning
confidence: 99%
“…The USFS highlighted two strategies for addressing climate change impacts on national forests: facilitated adaptation (i.e., actions for reducing the negative impacts of climate change) and mitigation (i.e., actions to reduce emissions and enhance natural carbon sequestration; Dillard et al 2008, Cruce andHolsinger 2010). interest groups (Lachapelle et al 2003, Jantarasami et al 2010, Wright 2010, and negative public perceptions (Archie et al 2012, Archie 2014. Transferring science between research and management can also be a challenge.…”
Section: Introductionmentioning
confidence: 99%